The first imported case of pulmonary coccidioidomycosis in Korea. - Jang, J. (Korean Academy of Medical Sciences, 1999)
Coccidioidomycosis is an endemic disease found in the southwestern part of North America. Travellers who visit the endemic area may carry the infection. We report a case of pulmonary coccidioidomycosis in a 74-year-old woman. She was healthy before visiting Arizona, U.S.A twice. After returning home, she began to complain of intermittent dry coughing. The symptom was mild, however, and she was treated symptomatically. Later a chest radiograph, which was taken 4 years after the onset of the symptom, showed a solitary pulmonary nodule in the right upper lobe. By percutaneous needle aspiration, a few clusters of atypical cells were noted in the necrotic background. A right upper and middle lobectomy was done. A 1.5 x 1.5 x 1.2 cm sized tan nodule was present in otherwise normal lung parenchyma. Microscopically, the nodule consisted of aggregates of multiple solid granulomas inside of which was mostly necrotic. Neutrophils and nuclear debris were scattered along the periphery of the necrotic foci. Numerous multinucleated giant cells were associated with the granulomas. In the necrotic area, mature spherules of Coccidioides immitis, which were 30-100 microm in diameter, were present. They contained numerous endospores which ranged from 5 to 15 microm and were also noted in multinucleated giant cells. The diagnosis of coccidioidomycosis was made. She is doing well after the resection.